Aplikasi Produk Geosintetik untuk Pekerjaan Reklamasi Pantai - Suhendra, Andryan (Bina Nusantara University, 2013)
Besides opening new land to the hilly terrain, reclamation of beach and other watery land is one of the alternatives of residential land compliance which is pretty much applied. However, the reclamation work often encounteres some obstacles, such as the soft subgrade with a low carrying capacity and the possibility for consolidation reduction which is large and long and high sea waves that could potentially cause abrasion during both construction and after construction. The use of geosynthetic materials as an alternative material supporting the reclamation work in Indonesia is still limited. The project owner and executives tend to use conventional methods though the use of geosynthetic can provide benefits and ease of implementation. Some of the advantages of using geosynthetic materials in reclamation work with soft soil foundation is a faster execution of the work, loss reduction of embankment material into the soft subgrade, and lower maintenance costs. This paper discusses geosynthetic products as well as its application to the reclamation work that comes with examples of projects that have been or are being carried out and in Indonesia.